The Effectiveness of Peer Review of Teaching when performed between Early-career Academics - Woodman, Richard; Parappilly, Maria (Journal of University Teaching and Learning Practice, 2015)
The success of peer review of teaching (PRT) in shaping teaching practice during an academic’s formative years may depend on the peers’ teaching experience and the frequency of evaluation. Two Australian early-career University lecturers with no previous experience of peer review performed a single PRT on one another following a one week academic development program, a mandatory exercise for all new academic staff with teaching roles within the University. Their experiences were recorded and used in the development of a teaching philosophy. The same PRT was then repeated between the same 2 individuals for the purpose of mandatory peer evaluation some 5 years later and after gaining considerable teaching experience. This paper describes the perceived impact of the PRT process on their teaching philosophies and the potential limitations imposed by their inexperience in formative PRT and teaching itself. Despite this relative inexperience, both academics believed their initial PRT accelerated changes to their mainly teacher-focused knowledge-transfer approaches. This case study provides qualitative evidence that PRT programs can successfully shape teaching practice without the involvement of more experienced teaching faculty. Academic developers should highlight the importance of building collegiality and the scholarship of teaching and learning for early-career PRT participants.